Estimation of Carbon Storage in Necromass in the Mangrove Area of Kayu Ara Permai Village, Siak Regency - Simanjuntak, Ezra Yehezkiel Rumegius; Siregar, Yusni Ikhwan; Siregar, Sofyan Husein (Department of Marine Science, Faculty of Fisheries and Marine Universitas Riau, 2026)
This research was conducted in March 2025 at the Mangrove Area of Kayu Ara Permai Village, Sungai Apit Subdistrict, Siak Regency. The study aimed to estimate the organic matter and carbon stocks of necromass and to determine the relationship between the number of necromass and its carbon stock. The method used was a survey, with purposive sampling, at three research stations. Measurements of organic matter and carbon stock of necromass were carried out using the volume method. The results showed that mangrove density ranged from 2,377.78 to 3,088.89 ind/ha, necromass organic matter ranged from 0.9676 to 2.1520 tons/ha, and necromass carbon stock ranged from 0.4548 to 1.0114 tons/ha. Based on the results of this study, there was a very weak positive correlation between necromass amount and its carbon stock, with a correlation coefficient (r) of 0.188.